PENGARUH PENDIDIKAN KEWIRAUSAHAAN, KECERDASAN ADVERSITAS, DAN DUKUNGAN SOSIAL TERHADAP INTENSI BERWIRAUSAHA PADA MAHASISWA KEWIRAUSAHAAN UNIVERSITAS MUHAMMADIYAH GRESIK - Erlinda, Calya Berliana Dewi; Respati, Putra Panji (POLITEKNIK LP3I JAKARTA, 2026)
The purpose of this study is to analyze the effect of entrepreneurship education, adversity intelligence, and social support on the entrepreneurial intentions of students in the Entrepreneurship Study Program at Muhammadiyah University Gresik. This study uses a quantitative approach with a survey method and total sampling technique. However, out of the 76 questionnaires distributed to the entire population, only 68 were returned and could be processed because they contained complete answers. Data collection was conducted using a Likert scale questionnaire from 1 to 5, and data analysis was performed using structural equation modeling (SEM) based on the partial least squares (PLS) method using SmartPLS 4. The results of the study indicate that entrepreneurship education has a positive and significant effect on entrepreneurial intention, which means that the better the learning experiences and entrepreneurial practices students obtain, the higher their intention to start their own business. However, intelligence in unfavorable conditions does not have a significant effect on entrepreneurial intention, which shows that students' ability to overcome difficulties is not a major factor in determining their entrepreneurial intention. On the other hand, it has been proven that social support has a positive and significant influence on entrepreneurial intention, mainly because most students receive support from family members who have entrepreneurial experience. Thus, this study emphasizes the importance of entrepreneurial education and social support as key external factors that shape students' entrepreneurial intention. The practical implication of this research is that Universities need to strengthen their applied entrepreneurship programs, provide business mentoring programs, and create a campus ecosystem that supports student business development.